2013
DOI: 10.1109/tuffc.2013.2782
|View full text |Cite
|
Sign up to set email alerts
|

Volume dependence in handel's model of quartz crystal resonator noise

Abstract: -Though criticized by many, Handel's quantum model for 1/f noise remains the only model giving a quantitative estimation of the level of intrinsic 1/f noise in quartz crystal resonators, compatible with the best experimental results. In this paper, we reconsider the volume dependence in this model. We first argue that an acoustic volume, representing the volume in which the vibration energy is trapped, should be used instead of the geometrical volume between the electrodes. Then, we show that since there is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…, (384) where V k are the harmonic amplitudes and v(φ)=V(φ)/V 1 is the normalized signal in eq. ( 375), from which the impulse sensitivity function ISF(φ) is…”
Section: The Occurrence Of High-order Harmonics Is Not Favorable For ...mentioning
confidence: 99%
See 1 more Smart Citation
“…, (384) where V k are the harmonic amplitudes and v(φ)=V(φ)/V 1 is the normalized signal in eq. ( 375), from which the impulse sensitivity function ISF(φ) is…”
Section: The Occurrence Of High-order Harmonics Is Not Favorable For ...mentioning
confidence: 99%
“…for lasers, by different mathematical treatment. Later works [383,384,385], however, indicated that vibration-wave nature of the crystals can produce 1/f noise, and, perhaps, there will soon be a reassessment of the approach for quantum noise, since some of the down-scaled devices are with dimensions similar to quantum devices, such as quantum dots and wires (e.g. CNT), and the noise in these devices is very large, see again Figure 51.…”
Section: Viii31 Length Uncertainty Variancesmentioning
confidence: 99%
“…The idea that the phase noise coefficient b −1 is proportional to 1/V, where V is the active volume, has been around for a while. In quartz resonators, this appears either directly or as a side effect of the larger size at lower frequency [27,28,29,30,31,32]. In ultrastable Fabry-Perot cavities, flicker is powered by thermal noise and proportional to the reciprocal of the length [33,34] which is approximately equivalent to 1/V after mechanical design rules.…”
Section: The Volume Lawmentioning
confidence: 99%